Handout of Pteridophyta of Sultan Adam Tahura area oriented to critical thinking ability of high school learners - Natalia La'lang Parura; Badruzsaufari Badruzsaufari; Suyidno Suyidno (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2024)
The Industrial Revolution 4.0 era requires every individual to think critically about various real-life problems, but these competencies are less trained in biology learning at school. This study aims to analyze the feasibility of the handout Pteridophyta Kawasasan Tahura Sultan Adam oriented critical thinking skills of high school students. This research includes research and development with the 4D model. Data were obtained through validation by 3 experts, responses of 8 students while using the handout on a limited trial, and 25 students on a broad trial. The characteristics of the handout developed compared to other teaching materials are that the teacher can develop it with a free format, practice questions in each sub-chapter of material, conclusion features in each reading, and real pictures that facilitate understanding of the material. The experts agreed that the handout developed had an average validity value of 4.3 with very valid criteria. In addition, students' responses to the Pteridophyta handout in the limited trial and broad trial were very good. Thus, the developed Pteridophyta handout is feasible to train critical thinking skills in biology learning.Abstrak. Era revolusi industri 4.0 menuntut setiap individu mampu berpikir kritis dalam menghadapi berbagai permasalahan kehidupan nyata, namun kompetensi tersebut kurang dilatihkan dalam pembelajaran biologi di sekolah. Penelitian ini bertujuan untuk menganalisis kelayakan handout Pteridophyta Kawasasan Tahura Sultan Adam berorientasi kemampuan berpikir kritis peserta didik tingkat SMA. Penelitian ini termasuk penelitian dan pengembangan dengan model 4D. Data diperoleh melalui validasi oleh 3 pakar, respon 8 peserta didik selama menggunakan handout pada uji coba terbatas dan 25 peserta didik pada uji coba luas. Karakteristik handout yang dikembangkan dibandingkan dengan bahan ajar lainnya adalah mampu dikembangkan sendiri oleh guru dengan format bebas, terdapat latihan soal disetiap sub bab materi, fitur kesimpulan disetiap bacaan dan gambar nyata yang mempermudah pemahaman materi. Para pakar sepakat bahwa handout yang dikembangkan memiliki nilai rata-rata validitas sebesar 4,3 dengan kriteria sangat valid. Selain itu, respon peserta didik terhadap handout Pteridophyta pada uji coba terbatas maupun uji coba luas dalam kriteria sangat baik. Dengan demikian, handout Pteridophyta yang dikembangkan adalah layak digunakan untuk melatihkan keterampilan berpikir kritis dalam pembelajaran biologi.